Manaraga – Władimir Sorokin i ostateczna dekonstrukcja tradycji literackiej - Łaniewski, Paweł (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The deconstruction of the literary tradition is one of the most frequently used postmodern motifs. It is the main point of many works of Russian postmodernists. Due to the exceptional achievements of Russian writers and the considerable influence on forming social consciousness their activity is subject to critical analysis in many works of all waves of Russian postmodernism. In this context Vladimir Sorokin's texts make their mark – for many of them the deconstruction of literary tradition and hermeneutics is a defining category.